Carbon Flows in Life Cycle Assessment of Carbon Capture Assessing Environmental Impacts and Carbon Capture Potential in Industrial Processes - Carlsson, William; Barclay, Jonathan (My University, 2023)
.This thesis presents a detailed analysis of the environmental impacts and carbon capture potential associated with cement production and biomass combustion. Through the use of life cycle assessment and material flow analysis, this study also offers a comprehensive understanding of the carbon capture and purification process within the PYROCO2 system, specifically focusing on a post-combustion amino solventbased approach. Additionally, the research explores opportunities for improving resource efficiency in the cement production process, aiming to the development of sustainable practices in these sectors. The findings of this research provide valuable insights into the potential of carbon capture technologies in mitigating climate change. The life cycle assessment results reveal the environmental impacts associated with cement production and biomass combustion, highlighting the potential of carbon capture methods in reducing emissions. By expanding the knowledge base on carbon capture and utilization technologies, this thesis contributes to the ongoing efforts to address climate change. The research outcomes aim to adopt sustainable practices and further advance carbon capture technologies to address the urgent challenge of climate change, which can contribute towards a more sustainable and carbon-neutral future.
Keywords: Life Cycle Assessment; Carbon Capture; Cement Production; Biomass Combustion; Carbon Flows; Environmental Impacts; Negative Emission Technology; openLCA